Policy Gap Analysis in the Implementation of the Mining Safety Management System (SMKP) in Mining Service Companies: A Qualitative Grounded Theory Approach - Rahman Arif; Aldri Frinaldi; Dasman Lanin; Rembrandt Rembrandt; Genius Umar; Nurhasan Syah (The Future of Education Journal, 2025)
Mining activities constitute a high-risk industry that requires the implementation of a structured, measurable safety management system in compliance with regulatory requirements. The Mining Safety Management System (SMKP) is mandatory for all mining companies and mining service companies as a primary instrument for protecting occupational safety and the environment. However, research findings at PT Adaro Tirta Sarana indicate that the level of SMKP implementation has only reached 57.08%, which remains below the minimum standard of 75% required by the PKP2B holder, PT Adaro Indonesia. This condition reflects a gap between policy formulation and implementation across various SMKP elements. This study employed a qualitative approach using open coding, axial coding, and selective coding techniques to identify the root causes of non-compliance in SMKP implementation. Data were collected through document reviews, interviews, field observations, and focus group discussions (FGDs) conducted in three operational areas involving eight key informants. The open coding results reveal that the main obstacles include policies that remain merely as documents without being translated into actionable programs, unmeasurable planning, mismatches in personnel competencies, operational implementation that does not comply with procedures, and weak evaluation and follow-up mechanisms. Through axial coding, these obstacles were categorized into four main groups: policy weaknesses, ineffective planning, inconsistent implementation, and low evaluation accountability. The core theme identified through selective coding indicates that the lack of integration of a safety culture within organizational governance is the primary factor contributing to the gap between policy and SMKP implementation. This study emphasizes the need to reformulate SMKP implementation, strengthen organizational safety structures, and optimize monitoring and evaluation systems to enhance compliance of mining service companies with applicable safety standards and regulations.